Inhibitory Effect of a Synthetic Prostacyclin Analogue, Beraprost, on Urokinase-type Plasminogen Activator Expression in RC-K8 Human Lymphoma Cells - Nomura, Naoki; Niiya, Kenji; Shinbo, Masahiro; Ozawa, Tetsuo; Hayakawa, Yumiko; Higashiyama, Ko-ichi; Fujimaki, Masao; Sakuragawa, Nobuo (Thrombosis and Haemostasis, 1996)
Plasminogen activation by urokinase-type plasminogen activator (uPA)is implicated in tumor invasion and metastasis by the breakdown of extracellular matrix. We have recently demonstrated the inhibitory effect of cAMP on uPA gene transcription in RC-K8 human lymphoma cells (Biochim Biophys Acta 1268: 293-9, 1995). Prostacyclin produced by endothelial cells is shown to increase cellular cAMP levels by activating adenylate cyclase. We, therefore, examined the effect of a stable analogue of prostacyclin, Beraprost, on uPA production in RC-K8 cells. uPA activity gradually increased in the conditioned medium with time. Beraprost (0.1 nM-1.0 μM) inhibited uPA accumulation in a dose-dependent manner without affecting cell viability. Fibrin-zymography demonstrated that high and low molecular forms of uPA were present in the conditioned medium and that after Beraprost-treat-ment all forms of uPA decreased and no PA/PA inhibitor complex was present. Northern blot analysis revealed that after exposure to Bera-prost, uPA mRNA levels increased transiently and then rapidly decreased to below control levels. Treatment with Beraprost resulted in a rapid activation of cellular cyclic AMP-dependent protein kinase (PKA). Beraprost completely negated uPA gene expression induced by phorbol myristate acetate, an activator of protein kinase C (PKC). These results suggest that Beraprost inhibits uPA production by suppressing uPA gene expression through the PKA pathway and that PKA-mediated signals are dominant in uPA gene expression as compared to those medicated by PKC. This inhibition of uPA expression by a prostacyclin analogue may be an important fact to explain the mechanism of anti-metastatic effects of prostacyclin.